Investigation of liquid crystalline property of a new calamitic liquid crystalline system methyl 4-(4ʹ-(4ʹʹ-(decyloxy)benzyloxy) benzylideneamino)benzoate. Issue 7 (28th May 2017) - Nandi, Rajib; Singh, Hemant Kumar; Singh, Sachin Kumar; Rao, D. S. Shankar; Prasad, S. Krishna; Singh, Bachcha; Singh, Ranjan K.
ABSTRACT: A new polar calamitic liquid crystal, methyl 4-(4ʹ-(4ʺ-(decyloxy)benzyloxy) benzylideneamino)benzoate (M3BA) containing ether and Schiff base groups as linker with terminal polar ester group, has been synthesised and mesomorphic properties are studied by differential scanning calorimetry, polarising optical microscopy, density functional theory, temperature-dependent X-ray diffraction and temperature-dependent micro- Raman study. The smectic A (SmA) mesophase with focal conic texture has been observed with wide mesomorphic range. Layer thickness in SmA phase is greater than the optimised length of the molecule, indicating partially bilayer SmA phase. Analysis of Raman marker bands of C–H in-plane bending of phenyl rings, C=C stretching of rings, C=N stretching and C=O stretching shows structural changes at molecular level at Cr → SmA phase transition and provides proper intermolecular interactions responsible for dimeric unit in partially bilayer SmA phase. Graphical Abstract: